The Effect of Distributive Justice and Job Embeddedness on Turnover Intention among Generation Z in Startup - Dea Nurdalina; Ira Hidayati; Rahmad Purnama (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2026)
High turnover intention among Generation Z employees poses a serious challenge for startup industries that rely on human resource stability and innovation. This study aims to examine the effect of distributive justice and job embeddedness on turnover intention among Generation Z employees in the startup industry. The research hypotheses propose that distributive justice and job embeddedness negatively affect turnover intention, both partially and simultaneously. This study employed a quantitative method with a correlational approach involving 175 Generation Z employees selected through purposive sampling. Data were collected using Likert-scale questionnaires and analyzed using multiple linear regression analysis. The results indicate that distributive justice and job embeddedness simultaneously have a significant effect on turnover intention, with distributive justice emerging as the dominant predictor. These findings highlight the importance of fair reward distribution and strengthening job embeddedness to reduce turnover intention among Generation Z employees in the startup sector.